Continuous chest compression cardiopulmonary resuscitation training promotes rescuer self-confidence and increased secondary training: a hospital-based randomized controlled trial - Blewer, Audrey L; Leary, Marion; Esposito, Emily C; Gonzalez, Mariana; Riegel, Barbara; Bobrow, Bentley J; Abella, Benjamin S (Critical care medicine, 2012)
Recent work suggests that delivery of continuous chest compression cardiopulmonary resuscitation is an acceptable layperson resuscitation strategy, although little is known about layperson preferences for training in continuous chest compression cardiopulmonary resuscitation. We hypothesized that continuous chest compression cardiopulmonary resuscitation education would lead to greater trainee confidence and would encourage wider dissemination of cardiopulmonary resuscitation skills compared to standard cardiopulmonary resuscitation training (30 compressions: two breaths). Prospective, multicenter randomized study. Three academic medical center inpatient wards. Adult family members or friends (≥ 18 yrs old) of inpatients admitted with cardiac-related diagnoses. In a multicenter randomized trial, family members of hospitalized patients were trained via the educational method of video self-instruction. Subjects were randomized to continuous chest compression cardiopulmonary resuscitation or standard cardiopulmonary resuscitation educational modes. Cardiopulmonary resuscitation performance data were collected using a cardiopulmonary resuscitation skill-reporting manikin. Trainee perspectives and secondary training rates were assessed through mixed qualitative and quantitative survey instruments. Chest compression performance was similar in both groups. The trainees in the continuous chest compression cardiopulmonary resuscitation group were significantly more likely to express a desire to share their training kit with others (152 of 207 [73%] vs. 133 of 199 [67%], p = .03). Subjects were contacted 1 month after initial enrollment to assess actual sharing, or "secondary training." Kits were shared with 2.0 ± 3.4 additional family members in the continuous chest compression cardiopulmonary resuscitation group vs. 1.2 ± 2.2 in the standard cardiopulmonary resuscitation group (p = .03). As a secondary result, trainees in the continuous chest compression cardiopulmonary resuscitation group were more likely to rate themselves "very comfortable" with the idea of using cardiopulmonary resuscitation skills in actual events than the standard cardiopulmonary resuscitation trainees (71 of 207 [34%] vs. 57 of 199 [28%], p = .08). Continuous chest compression cardiopulmonary resuscitation education resulted in a statistically significant increase in secondary training. This work suggests that implementation of video self-instruction training programs using continuous chest compression cardiopulmonary resuscitation may confer broader dissemination of life-saving skills and may promote rescuer comfort with newly acquired cardiopulmonary resuscitation knowledge. URL: http://clinicaltrials.gov. Unique identifier: NCT01260441.